2022
DOI: 10.1080/08897077.2021.1941506
|View full text |Cite
|
Sign up to set email alerts
|

“And Then the Rest Happened”— a Qualitative Exploration of the Role that Meaningful Activities Play in Recovery Processes for People with a Diagnosis of Substance use Disorder

Abstract: Bjornestad (2021): "And then the rest happened"-A qualitative exploration of the role that meaningful activities play in recovery processes for people with a diagnosis of substance use disorder, Substance Abuse,

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
10
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(20 citation statements)
references
References 35 publications
(67 reference statements)
2
10
1
Order By: Relevance
“…W20 (W8): Yes. This is consistent with earlier findings suggesting that meaningful activities are important for recovery processes because they promote social recovery capital (e.g., getting in touch with new communities), prevent substance use, and promote new positive experiences (Best et al, 2013;Davidson et al, 2006;Nordaunet & Saelør, 2018;Veseth et al, 2021;Weston et al, 2018). Moreover, these findings support a holistic, "all-inclusive" approach to meaningful activities in recovery (i.e., including all activities as equal and related to recovery), because personal interests are important for defining what is experienced and understood as meaningful.…”
Section: Meaningful Activities With Peerssupporting
confidence: 90%
See 4 more Smart Citations
“…W20 (W8): Yes. This is consistent with earlier findings suggesting that meaningful activities are important for recovery processes because they promote social recovery capital (e.g., getting in touch with new communities), prevent substance use, and promote new positive experiences (Best et al, 2013;Davidson et al, 2006;Nordaunet & Saelør, 2018;Veseth et al, 2021;Weston et al, 2018). Moreover, these findings support a holistic, "all-inclusive" approach to meaningful activities in recovery (i.e., including all activities as equal and related to recovery), because personal interests are important for defining what is experienced and understood as meaningful.…”
Section: Meaningful Activities With Peerssupporting
confidence: 90%
“…Future qualitative studies should use concrete questions about geographical PSOC (for question examples, see Bahl et al, 2021a) to investigate in-depth whether this reflects this population's neutral PSOC (i.e., a passive lack of feeling) (see Brodsky et al, 2002), the abstention dimension of NPSOC (i.e., uncaring attitude), or as suggested: a life stage-related lack of interest in geographical communities (Arnett, 2012;Gordon et al, 2020;Weiss-Dagan et al, 2021). Compared with previous, general samples with substance use problems, this sample reported that simply being around peers who were similar with respect to undergoing a recovery process was a central part of their understanding of meaningful activities, rather than connectedness and community member diversity (see Bahl et al, 2019;Nordaunet & Saelør, 2008;Veseth et al, 2021). Future research should investigate emerging adults' understandings of meaningful activities more deeply, to get a better understanding of necessities for recovery processes during this distinct life period.…”
Section: Limitations Strengths and Future Researchmentioning
confidence: 83%
See 3 more Smart Citations